Targeting Protein Kinases for the Treatment of Glioblastoma Multiforme: Linking Basic Studies to Clinical Applications - Zhou, Aidong (Current Pharmaceutical Design, 2017)
Glioblastoma multiforme (GBM) is the most common malignant primary brain tumor in adults with intensive heterogeneity and one of the most lethal human cancers. Protein kinases control diverse cellular processes by coordinating different signaling pathways. Protein kinases are frequently dysregulated in human cancers, which contributes to tumor initiation and development. Thus, protein kinases are a growing drug target class for cancers including glioblastoma. This review focuses on the most important protein kinases and kinase-mediated signaling cascades in glioblastoma, and discusses the functional mechanism of these kinases in glioblastoma tumorigenesis. Moreover, this review has summarized the most recent preclinical and clinical advances of agents targeting protein kinases in the treatment of glioblastoma.
Keywords: therapeutic strategy